Genetic diversity of Mycobacterium avium complex strains isolated in Argentina by MIRU-VNTR - Imperiale, Belen Rocio; Moyano, Roberto Damian; Di Giulio, A.B.; Romero, M.A.; Alvarado Pinedo, Maria Fiorella; Santangelo, María De La Paz; Travería, G.E.; Morcillo, N.S.; Romano, Maria Isabel (2017)
Mycobacterium avium sp. avium (MAA), M. avium sp. hominissuis (MAH), and M. avium sp. paratuberculosis (MAP) are the main members of the M. avium complex (MAC) causing diseases in several hosts. The aim of this study was to describe the genetic diversity of MAC isolated from different hosts. Twenty-six MAH and 61 MAP isolates were recovered from humans and cattle, respectively. GenoType CM® and IS1311-PCR were used to identify Mycobacterium species. The IS901-PCR was used to differentiate between MAH and MAA, while IS900-PCR was used to identify MAP. Genotyping was performed using a mycobacterial interspersed repetitive-unitvariable-number tandem-repeat (MIRU-VNTR) scheme (loci: 292, X3, 25, 47, 3, 7, 10, 32) and patterns (INMV) were assigned according to the MAC-INMV database (http://mac-inmv.tours. inra.fr/). Twenty-two (22/26, 84·6%) MAH isolates were genotyped and 16 were grouped into the following, INMV 92, INMV 121, INMV 97, INMV 103, INMV 50, and INMV 40. The loci X3 and 25 showed the largest diversity (D: 0·5844), and the global discriminatory index (Hunter and Gaston discriminatory index, HGDI) was 0·9300. MAP (100%) isolates were grouped into INMV 1, INMV 2, INMV 11, INMV 8, and INMV 5. The HGDI was 0·6984 and loci 292 and 7 had the largest D (0·6980 and 0·5050). MAH presented a higher D when compared with MAP. The MIRU-VNTR was a useful tool to describe the genetic diversity of both MAH and MAP as well as to identify six new MAH patterns that were conveniently reported to the MAC-INMV database. It was also demonstrated that, in the geographical region studied, human MAC cases were produced by MAH as there was no MAA found among the human clinical samples.